Mutation Load under Vegetative Reproduction and Cytoplasmic Inheritance - Kondrashov, A. S. (1994)
For reasons that remain unclear, even multicellular organisms usually originate from a single cell. Here I consider the balance between deleterious mutations and selection against them in a population with obligate vegetative reproduction, when every offspring is initiated by more than one cell of a parent. The mutation load depends on the genomic deleterious mutation rate U, strictness of selection, number of cells which initiate an offspring n, and the relatedness among the initial cells. The load grows with increasing U, n and strictness of selection, and declines when an offspring is initiated by more closely related cells. If Un >> 1, the load under obligate vegetative reproduction may be substantially higher than under sexual or asexual reproduction, which may account for its rarity. In nature obligate vegetative reproduction seems to be more common and long term in taxa whose cytological features ensure a relatively low load under it. The same model also describes the mutation load under two other modes of inheritance: (1) uniparental transmission of organelles and (2) reproduction by division of multinuclear cells, where each daughter cell receives many nuclei. The load declines substantially when the deleterious mutation rate per organelle genome gets lower or when the number of nuclei in a cell sometimes drops. This may explain the small sizes of organelle genomes in sexual lineages and the presence of karyonic cycles in asexual unicellular multinuclear eukaryotes.